Acute Toxicity Test Oral Effervecent Tablet Ethanol Extract of Ramania Leaves (Bouea macrophylla Griffith.) from South Kalimantan - Aryzki, Saftia; Budi, Setia; Yanti, Yanti (Universitas Muhammadiyah Surakarta, 2024)
Ramania (Bouea macrophylla Griffith.) is a herbal plant that has antioxidant properties and inhibits free radicals. This research aims to evaluate the safety of effervescent tablets of the ethanol extract of ramania leaves with acute toxicity test. The experimental animals used in this research were female Wistar white rats. The acute toxicity test was carried out orally using the fixed dose method in 4 groups of animals with dose groups of 50 (I), 300 (II), 2000 (III) and 5000 mg/kgBW (IV) respectively. Observations were made on the LD50, clinical condition, body weight and pathological condition of the test animals. The results of this study were that there were no animal deaths in all groups of test animals during observation. In clinical conditions, the 4 groups experienced discoloration and hair loss, while in groups III and IV the animals were inactive (weak). Based on the body weight of the test animals from the 4 observation groups, the sig value 0.05 means there is no significant change in the weight of the test group, on day 7 the values are 0.921 and 0.314, meaning there is no significant change in the weight of the test group. However, in the weight group 14 day with a value of 0.031, it means there is a significant difference to the weight of the test group. It can be concluded that the effervescent tablets of the ethanol extract of ramania leaves have an LD50 5000 mg/kg BW with a classification of non-toxic to animals.